(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Beauty holds a very important place in expressing the personality now-a-days. Clear and healthy skin makes a good impression. Everyone especially the young generations are most conscious and careful about the beauty of the face. Due to hurry, worry, and curry type of lifestyle and some hormonal factors in the adolescent age many people suffer through Acne. It is commonly seen in young population. Mukhadooshika, according to Ayurveda, can be correlated to acne. It is a type of Kshudraroga. It involves vitiation of Kapha and Vata along with Rakta resulting into formation of Mukhadooshika. Common sites are Mukha, Urah and Prushtha. In the management of Mukhadooshika, both Shodhan and Shaman chikitsa can be performed as per the Avastha. Vaman, Virechana, Raktamokshana, Nasya, Lepan etc. Panchakarma upakrama along with Abhyantar aushadhi chikitsa (internal medications) prove very effective in reducing the Mukhadooshika and preventing the recurrence. In this case study, a female patient with diagnosis of Mukhadooshika was treated with Virechana karma, Mukhalepa and Aushadhi chikitsa that showed marked improvement.